Anthelmintic Effects of Cassava (Manihot esculenta) Leaf extracts in The Haemonchus contortus In Vitro - Eva Ariyanti (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2012)
The resistance of gastrointestinal nematodes to anthelmintics has increased the need to evaluate natural products that can replace or assist current strategies to control gastrointestinal nematodes. The aim of this study is to determine anthelmintic effect of cassava (Manihot esculenta) on adult worms of Haemonchus contortus in vitro. Cassava leaves were dried at 55 °C, then grounded and lyophilised. Fifty grams of powder of leaf were extracted by 500 ml of hot distilled water and dried. Extract was made by percolation until filtrate produced. Filtrate was condensed with rotapavor at 48 °C with rotated at 200 rpm. Extracts were made into a concentration (w/v) of 25%, 50% and 75%.H. contortus were collected from an abomasum infected- lamb and put into 5 petri dish, 10 worms per petri dish in 2 ml of 37 °C NaCl. Each treatments with 5 replication. After 1hour, the NaCl was removed from each well and replaced by either one of the different concentrations of extracts 25%, 50% dan 75% or of the albendazole113,6 mg/ml positive control, or of the NaCl negative control. Observations were made under a magnifying glassevery 2 hours for a period of 6 hours to determine whether the adult worms were still alive or death. The results showed that extract of cassava leaf have anthelmintic effect on H. contortus. The increase of concentration 75% will result in a better effect. Compared to that of the negative control and positive control, signiﬁcant effects (P<0.05). The active chemical(s) responsible for the activity could be the tannin compounds present in the leaf.Key words :Anthelmentic, Haemonchus contortus, extracts, cassava leaves, tannin